How to conquer tax research: Making the most of online resources - Fong, Colin (School of Business Law, Curtin Business School, 2004)
The past ten years have seen enormous changes not only in terms of tax reform, but also in the way tax practitioners have acquired information about taxation. In addition to paper sources, electronic sources such as online services and CD ROMs have been boosted by resources available on the internet. Many documents which often took a long time to acquire are now readily available on the internet. Yes, but where? The aim of this paper is to highlight how tax research can be conducted using the internet and how to optimise your time in finding useful and relevant information. There is no one source for tax research. Many exist, and knowing where to look is the key.